A New Model for Heavy Metal Removal in a Biosorption Column - Guangyu Yan; T. Viraraghavan; Min Chen (Adsorption Science & Technology)
Column kinetics for metal removal could be described more adequately by a modified dose–response model than by the Thomas model or Bohart–Adams model conventionally used. The new empirical model can be used either in a linearized form or a non-linearized form. Use of the model minimizes the error resulting from use of the Thomas model, especially at lower or higher time periods of the breakthrough curve.